Potensi Batang Pisang (Musa Pardisiaca L.) Dalam Penyembuhan Luka Bakar - Gusti Putu Ananta (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Burn wounds appear as local response from tissue, with or without systemic response to energy transfer from physics source (mechanic, thermal, radiation, electricity) or chemical source. The impact are detrimental psycologically or physically to human. It is because this type of wound included in worst shaped-trauma that made human suffer since long ago and many years researcher did some trial to get improvement on burn wounds outcome from the series of treatment. This time, many plants in Indonesia not yet known to have efficacy in health. Banana (Musa paradisiaca L.) have a savor in wound healing. The result from previous research, showed that the banana stem extract contain of tannin, saponin, and flavonoid, which each of them have their own role in wound healing process. Saponin, this compound have antiseptic activity that help in wound healing. Flavonoid from flavonol, flavon, and isoflavon group have anti-inflammatory activity. Tanin is a polyphenols compound from flavonoid group that have function as a powerful antioxidant and also anti-inflammatory.